Purification of influenza viral complementary RNA: its genetic content and activity in wheat germ cell-free extracts. - Etkind, P R (1975)
Influenza viral complementary RNA (cRNA) was purified free from any detectable virion-type RNA (vRNA), and its genetic content and activity in wheat germ cell-free extracts were examined. After phenol-chloroform extraction of cytoplasmic fractions from infected cells, poly(A)-containing viral cRNA is found in two forms: in single-stranded RNA and associated with vRNA in partially and fully double-stranded RNA. To purify single-stranded cRNA free of these double-stranded forms, it was necessary to employ, as starting material, RNA fractions in which cRNA was predominantly single stranded. Two RNA fractions were successfully employed as starting material: polyribosomal RNA and the total cytoplasmic RNA from infected cells treated with 100 mug of cycloheximide (CM) per ml at 3 h after infection. In WSN virus-infected canine kidney (MDCK) cells, the addition of CM at 3 h after infection stimulates the production of cRNA threefold and causes a very large increase in the proportion of the cytoplasmic cRNA which is single stranded; double-stranded RNA forms are greatly reduced in amount. Total cRNA was obtained by oligo(dT)-cellulose chromatography, and single-stranded cRNA was separated from double-stranded forms by Sepharose 4B chromatography. The cRNA preparation purified from polyribosomes consists of 95% single-stranded cRNA, with the remaining 5% apparently being double-stranded RNA forms. The cRNA preparation purified from CM-treated cells (CM cRNA) is even more pure: 100% of the radiolabeled RNA is single-stranded cRNA. Annealing experiments, in which a limited amount of 32P-labeled genome RNA was annealed to the cRNA, indicate that the purified cRNA contains at least 84 to 90% of the genetic information in the vRNA genome. Purified viral cRNA (CM cRNA) is very active in directing the synthesis of virus-specific proteins in wheat germ cell-free extracts.